2008
DOI: 10.1016/j.tox.2008.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of dopamine uptake into rat striatal vesicles and synaptosomes caused by an in vitro exposure to atrazine and some of its metabolites

Abstract: Studies have shown that both in vivo and in vitro exposure to the herbicide atrazine (ATR) results in dopaminergic neurotoxicity manifested by decreased striatal dopamine (DA) levels. However, the mechanism behind this reduction is largely unknown. A decrease in striatal DA could be due to ATR exposure affecting vesicular and/or synaptosomal uptake resulting in disrupted vesicular storage and/ or cellular uptake of DA. Hence, we investigated the effects of in vitro ATR exposure on DA uptake into isolated rat s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 55 publications
1
29
1
Order By: Relevance
“…Using isolated synaptic vesicles preparations, we observed that ATR dose-dependently inhibited vesicular uptake of the neurotransmitter dopamine. The lowest effective concentration was 1 M (Hossain and Filipov, 2008), which is in the range of the brain ATR levels that we observed in the present study. DACT, at concentrations as high as 100 M, which is again in the range of the brain levels observed in the current study, was ineffective.…”
Section: Ross Et Alcontrasting
confidence: 43%
“…Using isolated synaptic vesicles preparations, we observed that ATR dose-dependently inhibited vesicular uptake of the neurotransmitter dopamine. The lowest effective concentration was 1 M (Hossain and Filipov, 2008), which is in the range of the brain ATR levels that we observed in the present study. DACT, at concentrations as high as 100 M, which is again in the range of the brain levels observed in the current study, was ineffective.…”
Section: Ross Et Alcontrasting
confidence: 43%
“…The only records available in literature refer to the neurotoxic kinetics of atrazine, a pesticide structurally similar to prometryne (23,24,26). Due to similar structure, the two compounds may share some toxicological properties (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Dosing was based previous toxicokinetic studies ( [22][23][24][25][26] that used doses higher than normally environmentally available to ensure detectable residue levels for our purposes.…”
Section: Treatment Of Experimental Animals With Prometrynementioning
confidence: 99%
“…There is an indication that the reduction in dopamine could be associated with a decrease in dopamine-producing neurons in the substantia nigra . Additionally, the uptake and sequestration of dopamine into vesicles appeared impaired and perhaps as a consequence of this, the ratio of dopamine metabolites/dopamine increased Hossain & Filipov, 2008). PC12 cells are neuronal cells derived from a tumour of the rat adrenal medulla that produce catecholamines including dopamine.…”
Section: Toxic Effects and Mechanism Of Actionmentioning
confidence: 99%